The Effect of Learning Media on Increasing Learning Motivation in terms of Creativity for Class X students in State Aliyah Madrasah in Kudus Regency - Wasino, Wasino; Hadromi, Hadromi; Wardana, Shony (Proceedings of International Conference on Science, Education, and Technology, 2025)
This research aims to find out: The difference of significant effect between the use of multimedia and worksheet media, high and low creativity levels on the students learning motivation. and the significant interaction effect between the use of learning media and the students' creativity level on the students learning motivation in MAN Kudus Regency. The research method employed was experimental method. The population of research were all grades X of MAN 1 and MAN 2 in Kudus Regency. The sample of research consisted of 1 class grade X of MAN 2 and 1 class of grade X of MAN 1 as the control group. The sampling was done using "Cluster Random Sampling". The instrument of data collection used was learning motivation and student creativity questionnaires. The validity of learning motivation questionnaire was tested using product moment formula while the reliability was tested using alpha formula. The creativity level questionnaire was not trialed because it is the result of research by SC Utami Munandar. Technique of analyzing data employed was Variance Analysis (ANOVA). The result of research shows that: There is difference of significant effect between the use of multimedia and worksheet media on the students learning motivation, There is difference of significant effect between high and low creativity levels on the students learning motivation, and there is no significant interaction effect between the use of learning media and the students' creativity level on the students learning motivation of grade X students of MAN in Kudus Regency.